A Visionary, Innovative, and Entrepreneurship Leadership In Increasing Local Government Performance - Saiful Rizal, Kemas; Leksono, Eko Budi; Agus, Rahmat (Profit: Jurnal Adminsitrasi Bisnis, 2023)
This study aims to reveal the meaning of Visionary, Innovative, and Entrepreneurial Leadership using the example of the Banyuwangi’s regent on 2010-2021. This research uses a qualitative method with a transcendental phenomenological approach by Edmund Husserl. In-dept interview has been conducted to dig information from employees of the local government, and community leaders. The researcher found three facts regarding the leadership’s style conducted by the local government. First, the implementation of the government’s programs which have been conducted define a meaning of the visionary leader. Second, the innovation on the programs altered and transformed Banyuwangi from the status of a witchcraft and transit city to a clean and beautiful tourist city. Third, a leader with an entrepreneurial spirit drives an improvement on the economic level and the development of SME in Banyuwangi. The programs have lifted the quality and quantity of tourist destinations which restore the image and reputation.